Investigation On Force Scaling For Multi Degree Of Freedom Bilateral Teleoperation Control System - Ahmad Zaki, Shukor; Jun Wei, Lee; Muhammad Herman , Jamaluddin (IJENS Publishers, 2016)
A bilateral control system consists of two actuation systems which are separate but sends and receives information to and from each other. Information shared consists of calculated force and position readings from sensors which feed into the control system. When the actuation systems are in the form of robot manipulators, there are at least two degrees of freedom with each degree of freedom has its own force and position values. When these two systems operate simultaneously, a change in force and position for one system triggers the other to coordinate and attempt to maintain the same values of force and position at both sides and this is termed as a master-slave system. In most cases, both systems are identical and the amount of force and position desired is similar. In some real-life applications, the desired amount of force/position is scaled; i.e. smaller or larger force is desired at one end of the system (master/slave). For this purpose, this research proposes a method to scale the force at either master or slave side by using elements of the mass/inertia matrix of the robot manipulator. Four different scaling values were demonstrated in the experiments to show the validity of the proposed method. Results indicate that the method is viable as the forces were scaled correctly as desired.